Interference Control Modulations Over Conscious Perception - Colás, Itsaso; Triviño, Mónica; Chica, Ana B. (Frontiers in Psychology, 2017)
The relation between attention and consciousness has been a controversial topic over the last decade. Although there seems to be an agreement on their distinction at the functional level, no consensus has been reached about attentional processes being or not necessary for conscious perception. Previous studies have explored the relation of alerting and orienting systems of attention and conscious perception, but the impact of the anterior executive attention system on conscious access remains unexplored. In the present study, we investigated the behavioral interaction between executive attention and conscious perception, testing control mechanisms both at stimulus-level representation and after error commission. We presented a classical Stroop task, manipulating the proportion of congruent and incongruent trials, and analyzed the effect of reactive and proactive control on the conscious perception of near-threshold stimuli. Reactive control elicited under high proportion congruent conditions influenced participants’ decision criterion, whereas proactive control elicited under low proportion congruent conditions was ineffective in modulating conscious perception. In addition, error commission affected both perceptual sensitivity to detect near-threshold information and response criterion. These results suggest that reactivation of task goals through reactive control strategies in conflict situations impacts decision stages of conscious processing, whereas interference control elicited by error commission impacts both perceptual sensitivity and decision stages of conscious processing. We discuss the implications of our results for the gateway hypothesis about attention and consciousness, as they showed that interference control (both at stimulus-level representation and after error commission) can modulate the conscious access of near-threshold stimuli.